The Effect of Job Design and Quality of Work Life on Affective Commitment of Vocational High School’s Teachers in East Jakarta Indonesia - Hanjarini, Gita Diana; Sugiarto, Sugiarto; Karnati, Neti (International Journal for Educational and Vocational Studies, 2020)
The purpose of this study is to comprehensively describe and describe the effect of work design and quality of work life on the affective commitment of vocational school teachers in East Jakarta. This research was conducted to Private Vocational High Schools (SMK) in East Jakarta. Methodology This study uses a quantitative research survey method, whereas for analyzing data using path analysis. Path analysis technique in this study is to determine the causal relationship between variables or the direct influence of exogenous variables on endogenous variables. Endogenous variables in this study are the teacher's affective commitment, while the exogenous variables in this study are work design and quality of work life. Data collection was carried out through questionnaire filling. Based on the calculation results obtained by path analysis 1) the direct effect of work design on affective commitment, the value of the path coefficient of 0.425 and tcount of 6.6964, meaning that work design has a direct positive effect on affective commitment can be accepted increasing work design resulting in increased affective commitment. 2) the direct effect of work design on the quality of work life, path coefficient of 0.225 and tcount of 3.378. Means, the direct influence of work design on affective commitment, the value of the path coefficient of 0.425 and tcount of 6.6964. 3) Work design has a direct positive effect on affective commitment can be accepted. That is, increasing work design results in increased affective commitment.